1983
DOI: 10.1016/0013-7944(83)90051-6
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanisms of fatigue crack growth retardation following overloads

Abstract: New mechanistic interpretations to rationalize fatigue crack growth retardation due to load excursions are presented. It is reasoned that crack closure arising from residual tensile displacements is not the primary mechanism for growth attenuation following a peak tensile overload.A new mechanism for retardation is discussed in terms of a "micro-roughness" model. Quantitative analyses are provided to estimate the extent of reducti ons ineffective dri vi ng force in the reta rded growth regi on due to possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(74 citation statements)
references
References 35 publications
5
67
0
2
Order By: Relevance
“…These results are consistent with those previously published [2,6,7,28,29], which mostly used the J integral as CDF parameter. Elasto-plastic stress analyses of bearings in operation have predicted LSY [30,31]; CTOD could thus prove to be a reliable indicator of crack growth under such conditions.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with those previously published [2,6,7,28,29], which mostly used the J integral as CDF parameter. Elasto-plastic stress analyses of bearings in operation have predicted LSY [30,31]; CTOD could thus prove to be a reliable indicator of crack growth under such conditions.…”
Section: Discussionsupporting
confidence: 93%
“…There is though some debate about which interactions cause crack retardation and acceleration and several hypotheses have been proposed as a source of these phenomena. There have been several reviews about load interactions on fatigue crack growth (4)(5)(6)(7)(8)(9)(10) which suggest that the principal reasons are: crack closure (plasticity, roughness and oxide), residual stresses, crack tip blunting, crack tip sharpening, crack tip branching, strain hardening, crack deflexion, and change in rate of damage accumulation in the reversed plastic zone ahead of the crack tip. All these interaction mechanisms depend on stress/strain conditions, material quality, load type, environment and other specific conditions that depend on the application.…”
Section: Introductionmentioning
confidence: 99%
“…Much effort has been given to the case of symmetrically bifurcated (forked) cracks [1]. Although many branches can be developed along the main crack path, it is experimentally observed that only the fastest branch continues to grow, while all others are brought to a stop due to the shielding caused by this fastest branch.…”
Section: Introductionmentioning
confidence: 99%